Animasi Interaktif Sebagai Media Pembelajaran Bahasa Inggris Menggunakan Metode ADDIE - Mia Rosmiati (LPPM Universitas Bina Sarana Informatika, 2019)
English is an international standard language used in conversations between countries. Therefore, learning English is very important given to children from an early age. However, in its implementation there are still many children who have difficulty learning English using learning methods that are difficult, less interesting and difficult. This learning media only relies on stationery such as books, paper, and pencils so that children increasingly like the learning process. Nowadays there are various interesting ways to attract children's interest in learning. One step that can be taken is to use computer technology as a medium for learning English for communication material with audio and visual material. Interactive animation is one form of learning method that uses audio visual media. In the world of education, animation has a role as a learning media that is quite interesting. Animation can increase interest in learning and understanding of certain fields of science. In addition, animation can also facilitate teachers in the learning process and also delivery material for students.